Impact of social networking towards employee job performance at Royal Malaysian Custom, Ayer Keroh, Malacca, Malaysia / Nor Salma Syuhada Md Noor , Nursyazhanis Habib and Sara Shezreen Mohd Ariff - Md Noor, Nor Salma Syuhada; Habib, Nursyazhanis; Mohd Ariff, Sara Shezreen (Faculty of Business and Management, 2012)
The study was conduct in order to identify the impact of social networking towards employee job performance at Royal Malaysian Custom, Ayer Keroh Melaka. The Royal Malaysia Custom allows the employees to access social network during working hours, Through the findings, there are three objectives of this study which are to identify the level of employee job performance at Malaysian Royal Custom, Ayer Keroh, to determine the impact between the use of social networking in the workplace and employee job performance at Malaysian Royal Custom, Ayer Keroh and to identify the factor most impact job performance at Malaysian Royal Custom, Ayer Keroh. The data that used in this study is primary data and the data collection that used was survey. The survey in this study used self-administered. The survey was in the form of a questionnaire. The questionnaire consists of 1 to 5 response scale. The questionnaire has responded were coded directly into SPSS Version 18.0 (Statistical Package for Social Science). The expected finding of this study is social networking during office hour does not effect the employee job performance. Social networking has positive impact on employee job performance through communication, collaboration and sharing information. There has used descriptive statistic to tested demographic session, used correlation pearson to tested the hypothesis and used regression to tested factor most impact on social networking. As a conclusion, there was significance value for the three of research objectives in this study in term of communication, collaboration and sharing information.